2020
DOI: 10.1007/s12551-020-00698-1
|View full text |Cite
|
Sign up to set email alerts
|

Biophysical characterization of dynamic structures of immunoglobulin G

Abstract: Immunoglobulin G (IgG) is a major antibody and functions as a hub linking specific antigen binding and recruitment of effector molecules typified by Fcγ receptors (FcγRs). These activities are associated primarily with interactions involving its Fab and Fc sites, respectively. An IgG molecule is characterized by a multiple domain modular structure with conserved N-glycosylation in Fc. The molecule displays significant freedom in internal motion on various spatiotemporal scales. The consequent conformational fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 69 publications
0
15
0
Order By: Relevance
“…There are five main isotypes of Abs found in humans: IgA, IgD, IgE, IgM and IgG. IgA and IgG are the most commonly used in therapeutics [25,27,28]. IgA are found in the mucosal membranes and help to prevent the colonization of mucosal pathogens.…”
Section: Antibody Structure and Functionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are five main isotypes of Abs found in humans: IgA, IgD, IgE, IgM and IgG. IgA and IgG are the most commonly used in therapeutics [25,27,28]. IgA are found in the mucosal membranes and help to prevent the colonization of mucosal pathogens.…”
Section: Antibody Structure and Functionmentioning
confidence: 99%
“…They are commonly found as dimers that take the shape of two Y's bound together at the stem [27]. IgG are considered memory Abs and provide the main Ab-based immunity against pathogens and comprise approximately 80% of total pooled Abs within humans [28]. Some antibodies, such as IgD, are membrane-bound and involved in cellular signaling.…”
Section: Antibody Structure and Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, the resolution of small-angle X-ray scattering (SAXS) is sufficient, especially when atomic structures of individual components are available, to determine the conformational variability of the antigen-binding fragments (Fabs) in various antibodies, 30 including complexes with antigens or Fc-gamma receptors (FcγRs). 31 , 32 A previous study showed that the Fabs’ conformational flexibility is derived from the inherent plasticity of the Fc-hinge regions in solution. 33 Rigidity of the hinges inversely correlates with, and can modulate mAb agonistic potency, 34 , 35 and this highlights the importance of newer strategies to modulate antibody-agglutination.…”
Section: Introductionmentioning
confidence: 99%
“…Although there have been several attempts by cryo-electron tomography ( Bongini et al, 2005 ; Jay et al, 2018 ; Lei et al, 2019 ; Sandin, Ofverstedt, Wikstrom, Wrange, & Skoglund, 2004 ), and negative stain electron tomography ( X. Zhang et al, 2015 ), large scale flexibility measurements are often not amenable to single-particle techniques. In contrast, the resolution of SAXS is sufficient (especially when atomic structures of individual components are available) to determine the Fab regions’ conformational variability in various antibodies, including complexes with antigens or Fc-gamma receptors (FcγRs) ( Wright, Elliston, Hui, & Perkins, 2019 ; Yanaka, Yogo, & Kato, 2020 ). A previous study showed that Fab regions’ conformational flexibility is derived from the Fc regions’ inherent plasticity in solution ( Remesh, Armstrong, Mahan, Luo, & Hammel, 2018 ).…”
Section: Introductionmentioning
confidence: 99%